2011
DOI: 10.1016/j.micpath.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis induces RANKL in bone marrow stromal cells: Involvement of the p38 MAPK

Abstract: Periodontitis is a bacterially-induced oral inflammatory disease that is characterised by tissue degradation and bone loss. Porphyromonas gingivalis is a gram negative bacterial species highly associated with the pathogenesis of chronic periodontitis. Receptor activator of nuclear factor-kB ligand (RANKL) induces bone resorption whilst osteoprotegerin (OPG) is a decoy receptor that blocks this process. Cyclooxygenase-2 (COX-2) is an enzyme responsible for the production of prostaglandin (PGE)(2,) which is a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Recently, other investigators have also shown that P. gingivalis induces NF κ B activation and p38 signaling for its actions [61, 62]. An inhibitor against MEK1/2 signaling pathway suppressed completely the IL-1 β -induced stimulation of NAMPT expression.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, other investigators have also shown that P. gingivalis induces NF κ B activation and p38 signaling for its actions [61, 62]. An inhibitor against MEK1/2 signaling pathway suppressed completely the IL-1 β -induced stimulation of NAMPT expression.…”
Section: Discussionmentioning
confidence: 92%
“…P. gingivalis can invade host cells and also evade the host defense system [6567]. As it has been shown in several cells that COX2, an enzyme which is responsible for the formation of prostanoids, is upregulated by P. gingivalis and IL-1 β , we also analyzed the COX2 expression as a positive control in our study [61, 62, 68, 69]. As expected, P. gingivalis and IL-1 β increased the COX2 expression in a dose- and time-dependent manner in PDL cells.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules play important roles in cell differentiation, proliferation and death [15], and are activated by phosphorylation of tyrosine/threonine residues in signal transduction cascades. Previous studies have shown that the p38 MAPK and ERK1/2 pathways are involved in the proliferation and differentiation of osteoblasts [1618]. Therefore, we hypothesized that ODN MT01 might regulate the differentiation of osteoblastic cells via the MAPKs pathway.…”
Section: Introductionmentioning
confidence: 93%
“…Experimental animals models of oral infection cannot efficiently represent human oral pathogenic bacteria, 15,16 whereas human experimental studies may answer questions regarding the initiation of these diseases, 17 but difficult to identify mechanisms that convert protective inflammation to tissue destructive lesion, due to ethical considerations. Most studies using in vitro models have only employed single oral bacterial species to challenge 2-dimensional monolayer cells, 18,19 or cells in suspension, [20][21][22] despite that periodontal infections are biofilm-related. 23 Moreover, monolayer cell culture systems do not adequately mimic the morphological and functional features of primary gingival tissues.…”
Section: Introductionmentioning
confidence: 99%